Fanar and the Serbian Orthodox Church - Milošević Zoran (Srpska Politička Misao)
When analyzing the relations of the Fanar - Patriarchy of Constantinople - towards the Serbian Orthodox Church, we have different periods. These are: periods of cooperation and periods of confrontation which were initiated by the Fanar. In this paper, we will talk about the period of confrontation. After the fall of the medieval Serbian state under the rule of the Ottoman Empire, the Orthodox found itself under the rule of the Muslims. Their position worsened with the abolition of the Patriarchate of Peć in 1766. It happened due to several things. The main reason cited is the mistrust of the Porte towards the Serbian Church and the work of the Fanariot Greeks who wanted to subjugate the Patriarchate of Peć to the Greek Church. The very act of abolition was preceded by attempts at Hellenization. It was not seen only in Serbia, but also in Bulgaria, where many learned Bulgarians considered themselves Greeks. Simultaneously with the arrival of Greek bishops at the head of the Serbian dioceses, the merciless plundering of the Serbian people began. It was one of the main reasons for the Islamization of not only the Serbs, but other peoples as well. The second period is contemporary. In it Fanar(iots) disputes the autocephaly of the Serbian Orthodox Church, as well as the territories under its jurisdiction. That is why they renamed it to the "Church of Serbia." Thereby taking away all dioceses outside the territory of the present-day state of Serbia from the Serbian Orthodox Church.